(untitled) (Research, Society and Development, 2022)
Objective: The objective of this study is to identify and analyze the scientific productions in the world literature on postoperative complications in elderly patients. Method: This is an integrative literature review whose data search was performed in different databases using the descriptors "Health of the Elderly", "Perioperative Care", "Postoperative Complications", "Patient Care" in the databases Electronic: Medical Literature Analysis and Retrieval System Online (MEDLINE) and Latin American and Caribbean Literature in Health Sciences (LILACS) via the Virtual Health Library (BVS). Scientific Electronic Library Online (SciELO), Web of Science (WOS), Cinahl and Scopus via CAPES Journal Portal and Cochrane Library. Results and Discussion: A total of 938 studies were identified in these databases. With 163 in Medline, 86 in LILACS, 73 in SciELO, 296 in the Scopus database, 208 in the Web of Science, 54 in the Cochrane Library and 58 in the CINAHL, after exclusion criteria, the final sample was 13 articles. Complications were observed in several surgical specialties, with the fragility in the health of the elderly being a potential for complications and increased hospital stay. Conclusion: The “age” factor predisposes to perioperative complications. Complications were observed in several surgical specialties, with the fragility in the health of the elderly being the potential for complications and increased hospital stay. Invasive and long-term procedures are increasingly being performed in the elderly. Anesthesia control and surveillance and hospital protocols are very useful in this phase.